MAINTENANCE COATING METHOD OF STEEL STRUCTURE AND CIRCULATION TYPE BLAST DEVICE USED THEREFOR - YAMADA SHOHEI; YAMADA HIROBUMI (2016)
PROBLEM TO BE SOLVED: To provide a maintenance coating method of a steel structure and a circulation type blast device used therefor, capable of largely shortening a construction period, and capable of also largely reducing cost.SOLUTION: A maintenance coating method uses a circulation type blast device 1 capable of injecting grit and a shot, and executes shot-peening processing by using the shot for improving fatigue strength to a blast-processed part of expressing a basis material surface, by executing blast processing by using the grit to a steel bridge K, and applies the final finish coating to a shot-peening-processed part thereafter.SELECTED DRAWING: Figure 2 【課題】工期を大幅に短縮でき、コストも大幅に縮小できる鋼構造物の保全塗装工法及びこれに用いられる循環式ブラスト装置を提供する。【解決手段】グリットとショットとを噴射可能な循環式ブラスト装置１を用いた保全塗装工法であって、鋼橋Ｋに対してグリットを用いてブラスト処理を行い、素地面が表出したブラスト処理済部分に対して疲労強度向上のためにショットを用いてショットピーニング処理を行い、その後、ショットピーニング処理済部分に対して最終仕上げ塗装を施すようにした。【選択図】図２